2017
DOI: 10.3389/fnins.2017.00155
|View full text |Cite
|
Sign up to set email alerts
|

Modified Mediterranean Diet for Enrichment of Short Chain Fatty Acids: Potential Adjunctive Therapeutic to Target Immune and Metabolic Dysfunction in Schizophrenia?

Abstract: Growing interest in gut and digestive processes and their potential link to brain and peripheral based inflammation or biobehavioral phenotypes has led to an increasing number of basic and translational scientific reports focused on the role of gut microbiota within the context of neuropsychiatric disorders. However, the effect of dietary modification on specific gut metabolites, in association with immune, metabolic, and psychopathological functioning in schizophrenia spectrum disorders has not been well char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 218 publications
(241 reference statements)
0
54
0
Order By: Relevance
“…Beneficial effects of the DASH dietary pattern on cardiometabolic parameters in people with and without diabetes mellitus were also confirmed in the recently conducted umbrella review by Chiavaroli et al [28]. However, studies on the relationship between the DASH diet and different health outcomes in people with schizophrenia are still insufficient and limited [29] and, to the best of our knowledge, there are no published RCTs evaluating the effects of the DASH diet on MetS in this specific population group.…”
Section: Introductionmentioning
confidence: 72%
“…Beneficial effects of the DASH dietary pattern on cardiometabolic parameters in people with and without diabetes mellitus were also confirmed in the recently conducted umbrella review by Chiavaroli et al [28]. However, studies on the relationship between the DASH diet and different health outcomes in people with schizophrenia are still insufficient and limited [29] and, to the best of our knowledge, there are no published RCTs evaluating the effects of the DASH diet on MetS in this specific population group.…”
Section: Introductionmentioning
confidence: 72%
“…Despite over 100-year history of research, the etiology of schizophrenia is still not fully understood, nonetheless, an interaction of environmental and genetic factors is still strongly considered (Joseph et al 2017, Nemani et al 2015. Schizophrenia typically develops at age between 15-45 years (Crow 1980) and has similar prevalence rates worldwide despite the different diagnostic criteria in various parts of the world (Arneth 2017, Sartorius et al 1986).…”
Section: Schizophreniamentioning
confidence: 99%
“…To make dietary interventions successful support from scientists, dieticians, family members, and neuropsychiatric clinicians is necessary (Joseph et al 2017). Further clinical trials are needed to confirm these theses.…”
Section: Schizophreniamentioning
confidence: 99%
“…In fact, several SCFAs produced by gut microbiota have been shown to be capable of potently inhibiting the formation of toxic soluble Aβ aggregates, in vitro [91]. A growing body of evidence has shown that circulating levels of SCFAs could affect CNS function [92,93], suggesting a functional role of SCFAs in the modulation of amyloidosis, neuroinflammation, and other AD-related conditions in the brain. Moreover, in the 3xTg-AD mice model (which rapidly develops amyloid plaques and NTFs) treated with the probiotics SLAB51, the levels of the bacterial metabolites (i.e., propionate and acetate) are elevated [55].…”
Section: Modulation Of Cns Function Mediated By Bacteria-derived Metamentioning
confidence: 99%